Factors Influencing Nurses` Intention to Leave Their Job in Benghazi Medical Center - Eman Alaqeli; Fathi Omar (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims: This study was conducted to identify factors that influence nurses’ intention to leave their job in Benghazi Medical Center (BMC), Libya. It was focused on the intrinsic and extrinsic factors of Herzberg’s theory that could affect the intention to leave the job. Based on the evidence in this field, there is an inverse relationship between job satisfaction and the intention to leave the job. Methods: A descriptive cross-sectional study was carried out. A nonprobability sampling technique was used. In total, 68 questionnaires were distributed and all of them were returned. SPSS was used to analyze the collected data. Results. About 30(44.1%) of nurses had an intention to leave their job. Females were more likely to leave their job than males. Additionally, there were significant relations between (gender and years of experience) and the intention to leave the job. Moreover, workload, recognition, and the monthly payment had a significant relationship with the intention to leave the job. Conclusion: The results in this study indicated nearly half of nurses had the intention to leave their job, and the main factors contributing to this issue were dissatisfaction with workload, recognition, and salary. Further efforts are recommended by hospital management to develop specific strategies that reduce nurses’ intention to leave their job and persuade them to remain in nursing.